Synthesis of Dodecyltrimethylammonium Bromochromate: An Improved Cr(VI)-Oxidant Reagent for Organic Substrates - Ghammamy, Shahriare; Imanieh, Hossein; K. Mohammady, Mohammad; Mazareey, Mahdi (Asian Journal of Chemistry, 2016)
Orange-brown crystalline dodecyltrimethylammonium bromochromate, (C12H25)N(CH3)3[CrO3Br], is easily prepared in a nearly quantitative yield by the interaction of dodecyltrimethylammonium bromide with CrO3 molar ratio. This reagent is versatile for the effective and selective oxidation of organic substrates, in particular for alcohols, under mild conditions. The reagent in CH2Cl2 readily oxidizes primary and secondary alcohols to the corresponding carbonyls, carbohydrate to ketosugre, anthracene and phenanthrene to anthraquinone and phenanthraquinone, respectively.